2004
DOI: 10.1038/nsmb735
|View full text |Cite
|
Sign up to set email alerts
|

Pam16 has an essential role in the mitochondrial protein import motor

Abstract: Mitochondrial preproteins destined for the matrix are translocated by two channel-forming transport machineries, the translocase of the outer membrane and the presequence translocase of the inner membrane. The presequence translocase-associated protein import motor (PAM) contains four essential subunits: the matrix heat shock protein 70 (mtHsp70) and its three cochaperones Mge1, Tim44 and Pam18. Here we report that the PAM contains a fifth essential subunit, Pam16 (encoded by Saccharomyces cerevisiae YJL104W),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
196
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 193 publications
(206 citation statements)
references
References 50 publications
8
196
0
2
Order By: Relevance
“…In vitro import into isolated yeast mitochondria (performed at 30°C), protease treatment of mitochondria, and carbonate extraction have been described previously Truscott et al, 2003;Frazier et al, 2004). Standard techniques were used for SDS-PAGE and Western blotting.…”
Section: Miscellaneousmentioning
confidence: 99%
“…In vitro import into isolated yeast mitochondria (performed at 30°C), protease treatment of mitochondria, and carbonate extraction have been described previously Truscott et al, 2003;Frazier et al, 2004). Standard techniques were used for SDS-PAGE and Western blotting.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Pam18 inactivation after precursor accumulation led to a similar loss of the TOM/TIM23 supercomplex, as observed in the ssc1-3 mutant. Although previous BN-PAGE analyses indicated that mtHsp70/Tim44 were not a stoichiometric constituents of the TOM/TIM23 supercomplex 25 , subsequent analyses showed that all constituents of the import motor are recovered with the TOM/ TIM23 supercomplex when mild affinity isolations are employed 13,[26][27][28][29][30] . Accordingly, at the active translocase, ATP hydrolysis by Hsp70, stimulated by its co-chaperone Pam18, was required to sustain the matrix-destined translocation intermediate.…”
Section: Import Motor Activity Maintains a Tom/tim23 Intermediatementioning
confidence: 90%
“…Therefore, impaired PAM machinery function leads to defects in the import of matrix-targeted proteins [28]. In case of Mgm1p, defective PAM function impairs the import of Mgm1p; therefore, the formation of the sMgm1p isoform was reduced [37] (Fig.…”
Section: The Pam Complex Mediates the Import Of Tm3-6 Of Mdl1pmentioning
confidence: 99%
“…Yeast transformants of W303-1a (MATa, ade2, can1, his3, leu2, trp1, ura3), W303-1a rho À [26], Dyta10 (MATa, ade2-1, his3-11,15, yta10::HIS3MX6, trp1-1, leu2,112, ura3-52) [27], the temperature-sensitive pam16-3 mutant or the isogenic wild-type PAM16 strain [28] carrying each plasmid were grown overnight in 5 ml of -Leu medium at 30°C. The preparation of whole-cell lysates by trichloroacetic acid (TCA) precipitation, SDS-PAGE and Western blotting were followed as described in [18].…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation